2007
DOI: 10.1210/jc.2006-0552
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Increases mRNA and Protein Expression of Na+-K+-ATPase α2 and β1 Subunits in Human Skeletal Muscles

Abstract: This provides the first evidence that, in human skeletal muscles, thyroid hormone up-regulates the Na+-K+-ATPase protein expression at least, in part, at mRNA level, and the alpha2 and beta1 subunits play the important role in this regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…These findings are consistent with the improved insulin sensitivity reported in developmental GHD and GH insensitive (GHRKO) mice [19][21], but are in contrast to the majority of clinical studies showing adults with GHD are insulin resistant [22][24]. These apparent species differences may be more related to diet, lifestyle, environmental factors and/or etiology and specificity of GHD, based on the finding that a rural Brazilian family with isolated GHD due to an inactivating mutation in the GHRH-R, were also found to be more insulin sensitive, as compared to their normal counterparts [25], [26]. In addition adult patients with Laron syndrome (inactivating mutations in the GH receptor) remained relatively insulin sensitive (calculated by HOMA-IR), despite an obese phenotype [27].…”
Section: Discussionmentioning
confidence: 95%
“…These findings are consistent with the improved insulin sensitivity reported in developmental GHD and GH insensitive (GHRKO) mice [19][21], but are in contrast to the majority of clinical studies showing adults with GHD are insulin resistant [22][24]. These apparent species differences may be more related to diet, lifestyle, environmental factors and/or etiology and specificity of GHD, based on the finding that a rural Brazilian family with isolated GHD due to an inactivating mutation in the GHRH-R, were also found to be more insulin sensitive, as compared to their normal counterparts [25], [26]. In addition adult patients with Laron syndrome (inactivating mutations in the GH receptor) remained relatively insulin sensitive (calculated by HOMA-IR), despite an obese phenotype [27].…”
Section: Discussionmentioning
confidence: 95%
“…A clinical study had revealed that the symptoms of TPP would be relieved after control of hyperthyroidism [15]. Thyroid hormone can stimulate Na + /K + -ATPase expression in skeletal muscle [16]. Moreover, excessive thyroxine supplement in a hypopituitarism patient after surgical treatment of craniopharyngioma could lead to periodic paralysis [17], indicating that high thyroid hormone levels can lead to TPP.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Thyroid response element (TRE) is present in some but not all isoforms of Na + , K + -ATPase subunits, and the stimulation by thyroid hormones may involve transcriptional as well as post-transcriptional mechanisms. 36,37 In general, the abundance of Na + , K + -ATPase is in good correlation with serum thyroid hormone levels.…”
Section: Na+ K+-atpase and Extracellular Potassium Homeostasismentioning
confidence: 99%
“…36,37 In general, the abundance of Na + , K + -ATPase is in good correlation with serum thyroid hormone levels. 35,38 …”
Section: Na+ K+-atpase and Extracellular Potassium Homeostasismentioning
confidence: 99%